Comparison of Outcomes in Patients With Muscle-invasive Bladder Cancer Treated With Radical Cystectomy Versus Bladder Preservation. (January 2019) - Zhong, Jim; Switchenko, Jeffrey; Jegadeesh, Naresh K.; Cassidy, Richard J.; Gillespie, Theresa W.; Master, Viraj; Nieh, Peter; Alemozaffar, Mehrdad; Kucuk, Omer; Carthon, Bradley; Filson, Christopher P.; Bilen, Mehmet A.; et al.
Abstract : Purpose: Radical cystectomy currently remains the standard of care for muscle-invasive bladder cancer. However, surgery can be associated with considerable morbidity and mortality, including the removal of the bladder. An alternative strategy is to preserve the bladder through concurrent chemoradiation following a maximal transurethral resection of the tumor. National protocols using a bladder-preservation approach have demonstrated disease-specific outcomes comparable to radical cystectomy in selected patients, but these results have not been replicated in previously reported population-based series. Here, we describe an outcomes analysis of patients with muscle-invasive bladder cancer treated with either radical surgery or bladder-preserving chemoradiation (BPCRT) for those patients meeting BPCRT criterion using the National Cancer Database (NCDB). Materials and Methods: Using the NCDB, patients with American Joint Commission on Cancer clinical T2-3, N0, M0 urothelial carcinoma diagnosed between 2004 and 2013 were included for analysis. Only patients treated with definitive intent with either radical cystectomy or concurrent chemotherapy and radiation after a maximal transurethral tumor resection were included. Propensity-score matching was used. Results: Among 8454 eligible patients, 7276 (86%) underwent radical cystectomy, and 1178 (14%) underwent BPCRT. Patients undergoing BPCRT were significantly older (median age, 77 vs. 68 y; P <0.001) and had higher Charlson-Deyo comorbidity scores ( P =0.002). Using propensity-matched analysis, 1002 patients remained in each cohort, and there was no significant difference in survival found between the 2 cohorts (median overall survival, 2.7 vs. 3.0 y [ P =0.20]; 4-year overall survival, 39.1% and 42.6% [ P =0.15], for BPCRT and surgery, respectively). In addition, the hazard ratio (HR) of surgery versus BPCRT decreased over time, with an initial HR of 1.27 favoring BPCRT which decreased by a factor of 0.85 per year. Conclusions: From 2004 to 2013, ∼14% of patients from the NCDB who potentially met bladder-preservation criteria underwent the procedure. Our propensity-matched analysis is the only report of its kind to demonstrate similar survival outcomes with bladder preservation when patients are properly selected. This study is also the first to demonstrate a dynamic HR between radical surgery and BPCRT over time.